Electrical Resilience in Residential Microgrids Powered by Biogas Micro-Combined Heat and Power (Micro-CHP) Systems - Iker De Loma-Osorio; David Borge-Diez (Engineering Proceedings)
The authors of this paper analyze the use of biogas-powered micro-Combined Heat and Power (micro-CHP) systems for residential microgrids to enhance their resilience during blackouts. With the increasing frequency of natural disasters, ensuring power system reliability has become a critical concern. Microgrids can provide a solution to this problem by integrating distributed energy resources and operating them independently of the grid. The authors of this paper investigate the design and implementation of biogas-powered micro-CHP systems for residential microgrids. The paper concludes with a discussion of the potential of biogas-powered micro-CHP systems as a key component of resilient and sustainable energy systems in the future.